Information Sharing and Communication Through Climate Change Images on Social Media - Akanda, A. K. M. Eamin Ali; Choudhury, Naziat (The Canadian Journal of Information and Library Science / La Revue canadienne des sciences de l’information et de bibliothéconomie)

(untitled) (Canadian Association for Information Science - Association canadienne des sciences de l'information, 2024)
In today’s world, the most popular and powerful tool to disseminate information on complex topics including climate change is social media. Information shared through various forms of texts and visual content on social media makes complicated topics easier to comprehend. The emotions, thoughts, and feelings expressed through images carry values that are far greater than those of texts. These features of images turn them into more meaningful content. People can be motivated to take action to establish and manage sustainable development. This research attempts to analyze the images posted on social media to build awareness among its users on climate change in Bangladesh. The accounts of Bangladeshi social media users are analyzed to find the various forms of images posted on social media and how people are engaging with these images. Also, social media users’ perspectives and awareness of climate change are studied here. Content analysis of 63 images on social media and semi-structured interviews with 10 social media users suggest that Bangladeshi social media users are focusing mostly on the impact of climate change, and less on its causes and solutions. Images containing the general public are more popular than images with political leaders, celebrities, and scientists which contradicts other findings. However social media users expressed less concern about the issue and believed that it is a matter of concern for the authority. Nevertheless, the younger generation in Bangladesh is taking a more active part in initiating actions to reduce the impact of climate change. As this younger generation ages, the future may bring positive changes if policies are made to support their initiatives.